Multi-scale cohesion force measurements for cemented granular materials - Farhat Abbas; Luu Li-Hua; Philippe Pierre; Cuéllar Pablo (EPJ Web of Conferences, 2021)
We experimentally investigated cohesion of artificially bonded granular materials made of spherical glass beads cemented by solid paraffin bonds. By means of laboratory tests designed and carried out for investigation at different scales, we measured the tensile yield strength for solid bonds both at the inter-particle micro-scale and cemented samples at the meso-scale. A parametric study has been performed by varying some of the granular material properties (bead diameter, paraffin content as well as the dimension of the sample for the meso-scale tensile tests. We finally propose a discusion on: (i) the relationship between the microscopic and macroscopic cohesion forces relying on classical homogenisation laws ; (ii) the potential impact of size effects based on a simple phenomenological model.